Legal Analysis of Legal Power and Legal Protection in Informed Consent Practices in High-Risk Surgical Procedures in Hospitals - Ediyanto; Markoni; Kanthika, I Made; Asri, Dyah Permata Budi (GoAcademica Research & Publishing, 2025)
This research examines the legal force and protective function of informed consent in high-risk surgical procedures, focusing particularly on the latest regulatory framework in Indonesia as stipulated by Law Number 17 of 2023 concerning Health. Currently, there is a notable absence of specific scholarly examination addressing this issue comprehensively. Although the regulation clearly defines patients’ rights to comprehensive medical information and mandates healthcare providers to deliver it transparently, practical ambiguities remain regarding the extent of informed consent’s binding legal authority and effectiveness in providing legal protection for both patients and medical professionals. Employing a normative juridical approach with descriptive-analytical methods, the study is primarily based on literature review and analysis of relevant Supreme Court decisions. The central objective of this research is to evaluate the legal enforceability and protective role of informed consent within the context of high-risk surgical treatments. The findings reveal that informed consent possesses substantial legal force derived from contractual principles established between patients and healthcare providers, thereby ensuring mutual legal protection during high-risk medical procedures. Informed consent encompasses preventive measures that aimed at averting potential disputes through clear communication, and repressive measures, which offer legal remedies in cases of violation, thus strengthening accountability and legal certainty within healthcare services.